Evaluation of acetylated histones 3 and 4 and histone deacetylases 1, 2 and 6 in cutaneous T-cell lymphoma in dogs - Matiz, Oscar Rodrigo Sierra [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
- Cutaneous lymphoma constitutes a form of extranodal lymphoma that affects initially the skin and/or adnexal structures and eventually presents an aggressive clinical behavior, causing internal organ infiltration in late-stage disease. The main immunophenotype is T-cell lymphoma (CTCL) and it represents the most common diagnosed type. It is expected that dogs with CTCL develop resistance to chemotherapy at any point during treatment, resulting in short survival times. A need for new therapeutic targets that improve survival expectation in dogs with CTCL is increasing. In humans, therapies based on epigenetic mechanisms helped to control the disease, since epigenetics became a main objective in the search for longer clinical responses in advance-stages. In the first two reported chapters, CTCL is described with particularities of international literature that contrast with data found in this institution, as well as, the role of epigenetics in the neoplasia carcinogenesis and the mechanism of histone modification as a base for treatment. More specifically, in the second chapter, 21 dogs with CTCL were defined as having high grade CTCL due to their large cell size, absence of epithelial tropism, mean value of Ki67 of 63,9% and estimated survival time of 31 days. Clinicopathological characteristics were analyzed for identifying prognostic markers, being the intrathoracic involvement caused by lymphoma seen on thoracic radiography an independent prognostic factor after multivariate analysis. In the last study, samples of CTCL were evaluated to know the level of acetylated histones (H3Ac and H4Ac) and histone deacetylate enzymes (HDAC) HDAC1, HDAC2 and HDAC6, which were involved in the epigenetic mechanism of histone modification in human CTCL. The objective of this study was to compare samples of CTCL in normal lymphnode, inflammatory cells in skin and normal epithelial cells. All markers (H3Ac, H4Ac, HDAC1, HDAC2 and HDAC6) were found to be higher in CTCL than in normal skin, furthermore, the level of H3Ac was statistically lower in CTCL than in normal lymphnode and an aberrant higher level of H4Ac and HDAC2 was confirmed in CTCL. Additionally, the association of the immunoexpression of H3Ac, H4Ac and HDAC2 classified into two the population, having different survival times (48 days Vs 22 days, p=0.06), suggesting that a histone profile exists in the studied population. This study confirmed that the level of histone deacetylases in CTCL are higher than in normal tissues. Further studies are needed to confirm our results and to support new research in HDAC inhibitors in dogs with CTCL.

O linfoma cutâneo constitui uma forma de linfoma extranodal que afeta inicialmente a pele e/ou anexos cutâneos e que pode apresentar um curso clínico agressivo, avançando a órgãos internos em estádios tardios. O principal imunofenótipo é de células T (LCCT) e representa a forma mais comumente diagnosticada. É esperado que os cães com LCCT desenvolvam resistência à quimioterapia em alguma etapa do tratamento, resultando em tempos curtos de sobrevida. Há uma necessidade por novos alvos de tratamento em cães com LCCT que consigam fornecer melhor expectativa de vida. Em humanos, medicações baseadas em mecanismos epigenéticos têm auxiliado no controle da doença sendo um alvo chave na procura de repostas clínicas mais douradoras em estádios avançados. Neste trabalho descreve-se, nos dois primeiros capítulos relatados, o LCCT e as particularidades descritas na literatura internacional que contrasta com os dados encontrados nesta instituição, assim como, o papel da epigenética na carcinogênese das neoplasias e o mecanismo de modificação de histonas como base para o tratamento. Mais especificamente, no segundo capítulo, foram analisados dados de 21 cães com linfoma cutâneo definido como LCCT de alto grau devido ao tamanho grande das células, à ausência de tropismo na epiderme, ao valor médio encontrado de Ki67 de 63,9% e ao tempo de sobrevida estimado de 31 dias. Características clinico-patológicas foram analisadas para a identificação de marcadores prognóstico, sendo definido as alterações decorrentes pelo linfoma vistas na radiografia como marcador prognóstico negativo independente depois da análise multivariada. No último capítulo relatado, amostras de LCCT foram avaliadas para conhecer o nível de histonas acetiladas (H3Ac e H4Ac) e de histonas deacetilases (HDAC) HDAC1, HDAC2 e HDAC6, as quais encontram-se envolvidas no mecanismo de modificação de histonas em LCCT de humanos. O objetivo desse estudo foi comparar amostras de LCCT com linfonodo normal, pele inflamada e pele normal de cães. Tanto as H3Ac e H4Ac como as HDAC1, HDAC2 e HDAC6 estiveram aumentadas em LCCT quando comparadas com pele normal, de igual maneira encontrou-se que o nível de H3Ac foi estatisticamente menor em linfoma que em linfonodo normal, e que um aumento aberrante de H4Ac e HDAC2 foi constatado em LCCT. Adicionalmente, evidenciou-se que a associação da imunoexpressão de H3Ac, H4Ac e HDAC2 classificou duas populações, as quais apresentaram tempos de sobrevida diferentes (48 dias Vs 22 dias, p=0.06), sugerindo assim um perfil de histonas existente em amostras de LCCT. Este estudo confirmou que o nível de histonas deacetilases em LCCT é maior que em tecidos saudáveis. Futuros estudos são necessários para corroborar nossos resultados e para que futuramente inibidores das HDAC possam ser utilizados em cães com LCCT.
Avaliação das histonas acetiladas 3 e 4 e das histonas desacetilases 1, 2 e 6 em linfoma cutâneo de células T em cães
Keywords: Epigenética; Oncologia; Enzimas; Linfoma